Sera of IgA nephropathy patients contain a heterogeneous population of relatively cationic alpha-heavy chains - Shuib, A.S.; Chua, C.T.; Hashim, Onn Haji (1998)
Sera of IgA nephropathy (IgAN) patients and normal subjects were analysed by two-dimensional (2-D) gel electrophoresis. Densitometric analysis of the 2-D gels of IgAN patients and normal subjects revealed that their protein maps were comparable. There was no shift of pI values in the major alpha-heavy chain spots. However, the volume of the alpha-heavy chain bands were differently distributed. Distribution was significantly lower at the anionic region in IgAN patients (mean anionic:cationic ratio of 1.184 +/- 0.311) as compared to normal healthy controls (mean anionic:cationic ratio of 2.139 +/- 0.538). Our data are in support of the previously reported findings that IgA1 of IgAN patients were lacking in sialic acid residues.